2018
DOI: 10.3389/fpsyg.2018.00727
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Barriers to Accessing Symptom-Specific Cognitive Behavior Therapy (CBT) for Distressing Voices: Reflecting on and Extending the Lessons Learnt From the CBT for Psychosis Literature

Abstract: The experience of hearing voices (‘auditory hallucinations’) can cause significant distress and disruption to quality of life for people with a psychosis diagnosis. Psychological therapy in the form of cognitive behavior therapy (CBT) for psychosis is recommended for the treatment of positive symptoms, including distressing voices, but is rarely available to patients in the United Kingdom. CBT for psychosis has recently evolved with the development of symptom-specific therapies that focus upon only one symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Further research in this area will be necessary to improve access to, and utility of, psychological therapy for those experiencing psychosis. Additional work by Hazell et al has suggested that symptom-specific treatment may be one route to overcoming the identified barriers (114).…”
Section: Toward Trauma-informed Treatment Options For Individuals Witmentioning
confidence: 99%
“…Further research in this area will be necessary to improve access to, and utility of, psychological therapy for those experiencing psychosis. Additional work by Hazell et al has suggested that symptom-specific treatment may be one route to overcoming the identified barriers (114).…”
Section: Toward Trauma-informed Treatment Options For Individuals Witmentioning
confidence: 99%
“…In patients with COPD, group CBT reduces patient-reported symptoms, increases exercise therapy, improves QoL, augments adherence to medical treatment and diminishes exacerbations [14, 15]. Despite these benefits, CBT remains underused in COPD patients, partly due to limited access for patients to CBT, and primary care providers not referring patients for CBT due to a paucity of knowledge, excessive waiting time and inadequate provision of psychological services [16, 17]. Furthermore, access to trained CBT therapists in the national health service is scarce.…”
mentioning
confidence: 99%
“…While there is consensus in the literature that CBT can significantly contribute to the effective management of schizophrenia and psychosis, access to this type of therapy is limited. 7,14 Furthermore, there may be a tendency in medical settings to prioritize medication management in dealing with troublesome psychiatric symptoms at the expense of attending to how patients think or interpret their symptoms. The idea of actually focusing on patients' thoughts and interpretations of their symptoms is comparatively new.…”
Section: Discussionmentioning
confidence: 99%
“…9,13 Despite evidence for its clear benefits, the availability of CBT for this population remains restricted. 7,14 Limited access to CBT specialists is an important barrier to its implementation, 15 as are restrictions linked to service management and delivery and to workforce capability and expertise. 16 Intensive case management (ICM) programs can improve access to CBT.…”
mentioning
confidence: 99%